PENGARUH PENGGUNAAN MEDIA BONEKA JARI PADA MATA PELAJARAN BAHASA INDONESIA TERHADAP KETERAMPILAN BERBICARA SISWA KELAS II SD INPRES OEPOI - Nurlailah; Fitriani Safina Langoday (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2023)
This study aims to determine the Effect of Finger Puppet Media on the Indonesian Language Subject on the Speaking Skills of Class II Students of SD Inpres Oepoi Academic Year 2019/2020. This research was carried out in Class II of SD Inpres Oepoi, Kupang City, which lasted for 2 (two) months from March to April 2020. The method used in this study was a quasi-experimental method consisting of two variables. The independent variable Finger Puppet Media and the dependent variable are students' speaking skills. The population in this study were all students of SDI Oepoi Kupang class II semester II 2019/2020 Academic Year, with samples from class IIA and class IIB. Class IIB was determined as the experimental class and class IIA as the control class. This sampling was determined using the Random Sampling technique, namely taking elements or samples randomly, where elements or members of the population have the same opportunity to be selected as samples. The data obtained were analyzed using descriptive and inferential statistics to determine normality, homogeneity and t-test to test the hypothesis. Posttest research results obtained t-test values at level α 0.05 with a df of 44 at a significant level of 0.000 <0.05, so it can be concluded that H0 is rejected and H1 is accepted. Thus it can be concluded that